On the inverse transfer of (non-)helical magnetic energy in a decaying magnetohydrodynamic turbulence - Park, Kiwan (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. In our conventional understanding, large-scale magnetic fields are thought to originate from an inverse cascade in the presence of magnetic helicity,
Gesehen am 12.06.2018